The Effect of Using Video Simulation and Hands-on Simulation Training on Preclinical Medical Students’ Confidence in Dermatological Suturing Skills - Alshaalan ZM (Dove Medical Press, 2022)
Ziad Mansour Alshaalan Department of Internal Medicine, Division of Dermatology, College of Medicine, Jouf University, Sakaka, Aljouf, Saudi ArabiaCorrespondence: Ziad Mansour Alshaalan, Department of Internal Medicine, Division of Dermatology, College of Medicine, Jouf University, Sakaka, Aljouf, 72388, Saudi Arabia, Tel +966-566000909, Email dr.ziad@ju.edu.saAim and Objectives: This study aimed to compare between the use of hands-on simulation training sessions versus video training on students' confidence in suturing skills. The study measured the effect of using hands-on simulation training versus video-recorded simulation training on medical students' suturing skills.Methods: This study was conducted at College of Medicine, Jouf University. All third-year medical students (n=98) were invited to participate in the study. However, only 81 (male=57, female=24) of them participated in this study. A randomized pretest-posttest control group study design was used to assess self-ratings of confidence in skills. All participants attended a lecture and were then divided into two groups: the experimental group (n=34) had simulation activities, while the control group (n=47) watched video-recorded training. A paired t-test was used to assess the difference between the pretest and post-test scores within each group. The independent t-test was used to compare the overall mean between both groups.Results: Statistically significant differences (improvements) of students' confidence in skills were detected in both groups. The mean difference between pre- and post-test scores for the experimental group was 1.47 (p< 0.001), and it was 0.92 (p< 0.001) for the control group.Conclusion: Both hands-on simulation training sessions and video training sessions are beneficial for teaching suturing skills for students. Furthermore, a long-term follow-up multicenter study that evaluates the impact of confidence in skin suturing skills on competence development is warranted among different university students in Saudi Arabia.Keywords: dermatology, Saudi Arabia, self-confidence, simulation, skills, students, suturing